Research progress on composition design and preparation technology of oxide dispersion strengthened steels for advanced nuclear energy systems - ZHAI Yazhong; CHE Hongyan; HE Xikou; BAO Hansheng (Fenmo yejin jishu)
Nuclear energy is a kind of clean energy, developing the Gen IV nuclear energy systems with higher safety and economy is the focus in current research. Traditional zirconium alloys have been unable to adapt to the harsh service environment of the Gen IV nuclear energy systems, and the development of materials with the excellent comprehensive properties has become an urgent problem in the field of nuclear energy engineering applications. The oxide dispersion strengthened steels (ODS) have been considered as the important candidate materials for the Gen IV nuclear energy system reactor cladding, due to the excellent comprehensive properties because of the reasonable composition design and unique microstructure. The high density dispersion oxide particles greatly improve the high temperature mechanical properties and radiation resistance of the alloys. Although a lot of research on the composition design-performance-preparation process of the ODS steels has been carried out around the world, there are still challenges in mass production, which restricts the engineering application of the ODS steels. The research on the microstructure, composition design, and preparation technology of the ODS steels at home and abroad was summarized and analyzed in this paper, the application prospect and existing problems of the ODS steels in the field of nuclear energy were prospected, providing the reference for the development of the nuclear grade ODS steels.